Authoritarian Environmentalism Undermined? Local Leaders' Time Horizons and Environmental Policy Implementation in China. (June 2014) - Eaton, Sarah; Kostka, Genia
Abstract China's national leaders see restructuring and diversification away from resource-based, energy intensive industries as central goals in the coming years. On the basis of extensive fieldwork in China between 2010 and 2012, we suggest that the high turnover of leading cadres at the local level may hinder state-led greening growth initiatives. Frequent cadre turnover is intended primarily to keep local Party secretaries and mayors on the move in order to promote the implementation of central directives. While rotation does seem to aid implementation by reducing coordination problems, there are also significant downsides to local leaders changing office every three to four years. Officials with short time horizons are likely to choose the path of least resistance in selecting quick, low-quality approaches to the implementation of environmental policies. We conclude that the perverse effects of local officials' short time horizons give reason to doubt the more optimistic claims about the advantages of China's model of environmental authoritarianism.